Irrigation Expansion and Rural Transformation in China: Evidence of Provincial Data in 1978–2018 - Pengfei Shi; Jikun Huang (Asia & the Pacific Policy Studies)
ABSTRACT The role of irrigation expansion in facilitating rural transformation has been widely documented, yet quantitative studies remain rather limited. Based on the statistical data from 27 provinces in China, this paper analyses the correlation between irrigation expansion and rural transformation over the period of 1978–2018. The econometric results indicate a positive relationship between irrigation expansion and high‐value agriculture. However, from a dynamic perspective, for each percentage point increase in the share of cultivated land with irrigation, the share of high‐value agriculture decreases by 0.09 percentage points in the early stage, but increases by 0.07 and 0.12 percentage points in the subsequent middle and later stages, respectively. Likewise, the relationship between irrigation expansion and non‐farm employment of rural labourers is not always negative. Specifically, an additional one percentage point increase in the share of cultivated land with irrigation is associated with a 0.09 percentage points decline in the share of rural labour non‐farm employment in the early stage. This reduction moderates to a 0.05 percentage points in the middle stage, but there is a 0.08 percentage points increase in the later stage. This paper further concludes with several implications for policymakers and academic research.